2019
DOI: 10.1088/1741-2552/ab5299
|View full text |Cite
|
Sign up to set email alerts
|

Improved visual acuity using a retinal implant and an optimized stimulation strategy

Abstract: Objective. Retinal prosthetic devices hold great promise for the treatment of retinal degenerative diseases such as retinitis pigmentosa and age-related macular degeneration. Through electrical stimulation of the surviving retinal neurons, these devices evoke visual signals that are then relayed to the brain. Currently, the visual prostheses used in clinical trials have few electrodes, thus limiting visual acuity. Electrode arrays with high electrode densities have been developed using novel technologies, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 71 publications
(153 reference statements)
6
44
0
Order By: Relevance
“…Both simulation and experimental results also indicate that more charge or current will be required for neural stimulation when using local returns, due to the decrease of electric field intensity (Tong et al, 2019a). The elevated thresholds will lead to larger power consumption and a greater charge requirement for the electrodes.…”
Section: Spatial Resolutionmentioning
confidence: 96%
See 4 more Smart Citations
“…Both simulation and experimental results also indicate that more charge or current will be required for neural stimulation when using local returns, due to the decrease of electric field intensity (Tong et al, 2019a). The elevated thresholds will lead to larger power consumption and a greater charge requirement for the electrodes.…”
Section: Spatial Resolutionmentioning
confidence: 96%
“…Multicell bolus loading (Borghuis et al, 2011) using membrane permeable indicators was reported but uniform staining was difficult. Other methods that successfully stained RGCs in mammalian retinas include electroporation (Baden et al, 2016), dye incubation after dissolving the ILMs (Cameron et al, 2016), direct dye injection into the optic nerve (Tong et al, 2019a), and transduction with genetically encoded calcium indicators through adenoassociated viral vectors (Weitz et al, 2015). To reveal the activities of degenerated photoreceptors to electrical stimulation, incubation of retina with cell permeable dyes has been reported (Haq et al, 2018).…”
Section: Optical Imagingmentioning
confidence: 99%
See 3 more Smart Citations